Matrotrophy and placentation in invertebrates: a new paradigm. (29th April 2015) - Ostrovsky, Andrew N.; Lidgard, Scott; Gordon, Dennis P.; Schwaha, Thomas; Genikhovich, Grigory; Ereskovsky, Alexander V.
ABSTRACT: Matrotrophy, the continuous extra‐vitelline supply of nutrients from the parent to the progeny during gestation, is one of the masterpieces of nature, contributing to offspring fitness and often correlated with evolutionary diversification. The most elaborate form of matrotrophy—placentotrophy—is well known for its broad occurrence among vertebrates, but the comparative distribution and structural diversity of matrotrophic expression among invertebrates is wanting. In the first comprehensive analysis of matrotrophy across the animal kingdom, we report that regardless of the degree of expression, it is established or inferred in at least 21 of 34 animal phyla, significantly exceeding previous accounts and changing the old paradigm that these phenomena are infrequent among invertebrates. In 10 phyla, matrotrophy is represented by only one or a few species, whereas in 11 it is either not uncommon or widespread and even pervasive. Among invertebrate phyla, Platyhelminthes, Arthropoda and Bryozoa dominate, with 162, 83 and 53 partly or wholly matrotrophic families, respectively. In comparison, Chordata has more than 220 families that include or consist entirely of matrotrophic species. We analysed the distribution of reproductive patterns among and within invertebrate phyla using recently published molecular phylogenies: matrotrophy has seemingly evolved at least 140 times in all major superclades: Parazoa and Eumetazoa, Radiata and Bilateria, Protostomia and Deuterostomia, Lophotrochozoa and Ecdysozoa. In Cycliophora and some Digenea, it may have evolved twice in the same life cycle. The provisioning of developing young is associated with almost all known types of incubation chambers, with matrotrophic viviparity more widespread (20 phyla) than brooding (10 phyla). In nine phyla, both matrotrophic incubation types are present. Matrotrophy is expressed in five nutritive modes, of which histotrophy and placentotrophy are most prevalent. Oophagy, embryophagy and histophagy are rarer, plausibly evolving through heterochronous development of the embryonic mouthparts and digestive system. During gestation, matrotrophic modes can shift, intergrade, and be performed simultaneously. Invertebrate matrotrophic adaptations are less complex structurally than in chordates, but they are more diverse, being formed either by a parent, embryo, or both. In a broad and still preliminary sense, there are indications of trends or grades of evolutionarily increasing complexity of nutritive structures: formation of ( i ) local zones of enhanced nutritional transport (placental analogues), including specialized parent–offspring cell complexes and various appendages increasing the entire secreting and absorbing surfaces as well as the contact surface between embryo and parent, ( ii ) compartmentalization of the common incubatory space into more compact and 'isolated' chambers with presumably more effective nutritional relationships, and ( iii ) internal secretory ('milk') glands. Some placental analogues in onychophorans and arthropods mimic the simplest placental variants in vertebrates, comprising striking examples of convergent evolution acting at all levels—positional, structural and physiological.